Researching literacy policy: Conceptualizing trends in the field. (30th June 2021) - Innes, Mark; Gunter, Helen M.; Armstrong, Paul
Abstract : page_1 other The Literacy Policy Project examines the trends in UK government policy interventions into literacy curriculum and pedagogies in schools in England. We undertake a policy scholarship methodology to read policy texts through a conceptual framework that frames policy interventions with functional, realist or socially critical purposes. We identify how successive UK governments have primarily adopted functional policies and research relating to literacy in schools in England. We argue that policy is dictated by, and serves, a growing marketplace for educational solutions, making the case that more prominence should be given to facilitating socially critical approaches to literacy policy.